Biological fuel. Problems and prospects - Ranskyi, A. P.; Tkachuk, M. F.; Tiutiunnyk, L. M.; Alpatova, N. V.; Ranska, A. A.; Petruk, R. V.; Boiko, S. R. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problems and prospects of biofuels usage, as a renewable energy source, in the world and in Ukraine. Technological aspects of production and industrial use of bioethanol and biodizel have been analyzed.